A Preliminary Design For E-Dua Application - Mesbahul Hoque; Al Jannah Abdullah; Zuriah Ikah (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.